(untitled) (Revista Electrónica REDINE, 2018)
The past and the present of art show evidence of the avocados artists to a transformation of the human body through different ideas that integrate artificial elements. The use of implants, body cloning and gender redistribution increasingly project a transgression to society until questioning and educating it. The body becomes the image, in the reflection of what we are and are not, so Sterlac, Orlan and Algeria Bra vo transpose the knowable world in another way implanting concepts from the artistic realm that transform the future beyond humanity itself , The transhuman. The action art brings us from the past to characters like Sterlac, who in the interventions of his own body with incisions and implants that hear his ideas, his third ear in the arm are examples of a need for change. On the other hand, perhaps with an influence of feminism and social criticism, Orlan ceases to be her and transforms herself into all the women in one who are objects of desire and admiration, close to the sublime that Kant proposes, sells his object of the performances since The surgical intervention rooms to the world while she perpetuates her implants. In Venezuela Algeria Bravo, she takes advantage of this space between sex, or transhuman, beyond the biological convention, proposed pink prints on canvas of a different body, of an upper and lower masculine body, referring to the same body and its physiognomic members. Three art ists who present the other convention, of existence of a body, of many bodies, of the being beyond the human.